Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the equation [tex]\(x = \sqrt{x + 30}\)[/tex] for [tex]\(x\)[/tex], follow these steps:
1. Isolate the square root: The square root is already isolated in the given equation [tex]\(x = \sqrt{x + 30}\)[/tex].
2. Square both sides to eliminate the square root. Squaring both sides of the equation yields:
[tex]\[ x^2 = (\sqrt{x + 30})^2 \][/tex]
Which simplifies to:
[tex]\[ x^2 = x + 30 \][/tex]
3. Rearrange the equation to form a standard quadratic equation. To do this, move all terms to one side of the equation:
[tex]\[ x^2 - x - 30 = 0 \][/tex]
4. Factor the quadratic equation [tex]\(x^2 - x - 30 = 0\)[/tex]. To factor this, we need to find two numbers that multiply to [tex]\(-30\)[/tex] and add up to [tex]\(-1\)[/tex]. Those numbers are [tex]\(6\)[/tex] and [tex]\(-5\)[/tex]:
[tex]\[ x^2 - x - 30 = (x - 6)(x + 5) = 0 \][/tex]
5. Set each factor equal to zero to solve for [tex]\(x\)[/tex]:
[tex]\[ x - 6 = 0 \quad \text{or} \quad x + 5 = 0 \][/tex]
6. Solve each equation:
[tex]\[ x - 6 = 0 \implies x = 6 \][/tex]
[tex]\[ x + 5 = 0 \implies x = -5 \][/tex]
7. Check each potential solution in the original equation to ensure they are valid.
- For [tex]\(x = 6\)[/tex]:
[tex]\[ 6 = \sqrt{6 + 30} \][/tex]
[tex]\[ 6 = \sqrt{36} \][/tex]
[tex]\[ 6 = 6 \][/tex]
This is true.
- For [tex]\(x = -5\)[/tex]:
[tex]\[ -5 = \sqrt{-5 + 30} \][/tex]
[tex]\[ -5 = \sqrt{25} \][/tex]
[tex]\[ -5 = 5 \][/tex]
This is false, as [tex]\(-5\)[/tex] does not equal [tex]\(5\)[/tex].
Hence, the only valid solution is:
[tex]\[ x = 6 \][/tex]
1. Isolate the square root: The square root is already isolated in the given equation [tex]\(x = \sqrt{x + 30}\)[/tex].
2. Square both sides to eliminate the square root. Squaring both sides of the equation yields:
[tex]\[ x^2 = (\sqrt{x + 30})^2 \][/tex]
Which simplifies to:
[tex]\[ x^2 = x + 30 \][/tex]
3. Rearrange the equation to form a standard quadratic equation. To do this, move all terms to one side of the equation:
[tex]\[ x^2 - x - 30 = 0 \][/tex]
4. Factor the quadratic equation [tex]\(x^2 - x - 30 = 0\)[/tex]. To factor this, we need to find two numbers that multiply to [tex]\(-30\)[/tex] and add up to [tex]\(-1\)[/tex]. Those numbers are [tex]\(6\)[/tex] and [tex]\(-5\)[/tex]:
[tex]\[ x^2 - x - 30 = (x - 6)(x + 5) = 0 \][/tex]
5. Set each factor equal to zero to solve for [tex]\(x\)[/tex]:
[tex]\[ x - 6 = 0 \quad \text{or} \quad x + 5 = 0 \][/tex]
6. Solve each equation:
[tex]\[ x - 6 = 0 \implies x = 6 \][/tex]
[tex]\[ x + 5 = 0 \implies x = -5 \][/tex]
7. Check each potential solution in the original equation to ensure they are valid.
- For [tex]\(x = 6\)[/tex]:
[tex]\[ 6 = \sqrt{6 + 30} \][/tex]
[tex]\[ 6 = \sqrt{36} \][/tex]
[tex]\[ 6 = 6 \][/tex]
This is true.
- For [tex]\(x = -5\)[/tex]:
[tex]\[ -5 = \sqrt{-5 + 30} \][/tex]
[tex]\[ -5 = \sqrt{25} \][/tex]
[tex]\[ -5 = 5 \][/tex]
This is false, as [tex]\(-5\)[/tex] does not equal [tex]\(5\)[/tex].
Hence, the only valid solution is:
[tex]\[ x = 6 \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.